(untitled) (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
Fear in eco-turbulence captures the real picture of the present global warming’s, chemical issues, industrial smokes, pollution in different fields and the fear of the environment and the exports who want to avoid such possible disasters for the living creatures. It has attempted to present the facts as it is to give the true knowledge to those people who have no knowledge in this regard. It shows that lots of experts have already warned people to be conscious in it and to address the issues on time for the sake of humanity. It does not blame anyone but awakens the people of all levels to come in the action of preserving and balancing ecology and environment in no time.